INFORMATION ON MOTIVATION, COMPENSATION, WORK ENVIRONMENT AND ITS IMPACT ON THE PERFORMANCE OF SHARIA BANK EMPLOYEES - Zahera Mega Utama; Mas Wigrantoro; Watriningsih Watriningsih (STMIK Dharma Wacana, 2023)
Competition of financial institutions is so tight, however the development of Islamic financial institutions the longer shows that the positive trend. The basic problem in islamic bank is how to spur employee performance to always improve. Excellent employees will contribute significantly to achieve the company’s goals. Bank Syariah Indonesia (BSI) have been experiencing a significant growth. This research purposes to know the effect of motivation, compensation and work environment on employee performance at BSI KCP Pancor. The research used the quantitative with correlation method. The sample is collected by using saturated sampling method and multiple linear regression for analyzing the data. The number of samples used in this study amounted to 30 respondents source was distribution of questionnaires to BSI employees. This study found that Motivation (0,032<0,05), Compensation (0,021<0,05) and Work Environment (0,044<0,05) has significant and positive effect on employee performance at BSI KCP Pancor. This study assists to understand the bank management specifically in employee performance. In other hand, the findings can be preferences in making policy for government, helpful to use additional references about comparison of Islamic banks employee performance and its influence.